Female mate choice and male–male competition in Tonkean macaques: Who decides?. (May 2017) - Rebout, Nancy; Thierry, Bernard; Sanna, Andrea; Cozzolino, Roberto; Aujard, Fabienne; De Marco, Arianna
Abstract: The theory of sexual selection predicts that females should be discriminatory in the choice of sexual partners. Females can express their choice in two ways. In direct mate choice, they show preferences for certain partners. In indirect mate choice, they select partners by displaying sexually attractive traits, thus eliciting contest competition between males. We focused on a primate species in which females advertise the timing of their ovulation and studied the balance between these two choice strategies. We tested predictions related to three hypotheses about direct and indirect female choice, namely the best‐male, graded‐signal and weak‐selectivity hypotheses. We investigated the sexual and agonistic interactions occurring during oestrous periods in five captive groups of Tonkean macaques ( Macaca tonkeana ). The results showed that dominant males used mate guarding to monopolise sexual access to parous females that were in the fertile stage of their reproductive cycle, while lower‐ranking males monitored only nulliparous females. The distribution of sexual presentations indicated that females accepted different types of partners, supporting the weak‐selectivity hypothesis regarding direct mate choice. The analysis of behavioural sequences revealed that mate‐guarding males used mild coercive behaviours to prevent females from mating with other males at conception time. The distribution of mounts showed that females mainly mated with dominant males, which leads us to argue that the best‐male hypothesis provides the most parsimonious explanation regarding indirect mate choice in Tonkean macaques. At the individual level, it may be concluded that male competitive strategies prevented females from exercising direct mate choice. At the evolutionary level, however, female sexual advertising and thus indirect choice promoted competition between males. The outcome is that indirect mate choice appears more important than direct mate choice in female Tonkean macaques.